Sosialisasi Persiapan Volunteer pada Event AUG Volunteer Orientation for the AUG Event - Nur Salsabila Rhesa P. P.; Hapsari Shinta Citra Puspita Dewi; Nur Shanti Retno Pembayun (Jurnal Informasi Pengabdian Masyarakat, 2026)
The ASEAN University Games (AUG) 2024 is a Southeast Asian multi-sport event held in Surabaya and Malang from June 25 to July 6, 2024. The success of this international event largely depends on the readiness of human resources, particularly volunteers who serve as the frontline in providing services to athletes, officials, and international guests. However, prospective volunteers faced several challenges, including limited understanding of their roles and responsibilities, uneven technical preparedness, inadequate cross-cultural communication skills, and insufficient non-technical training to support professional service delivery. These conditions could hinder coordination and reduce service quality during the event. This community service program aimed to improve volunteer readiness and competence through structured socialization and training activities. The program was implemented using the ADDIE approach, consisting of Analyze, Design, Develop, Implement, and Evaluate. The training covered volunteer roles and responsibilities, technical skills, emergency response simulations, soft skills development, cross-cultural communication, motivation management, and participant readiness evaluation. The activity involved 40 SMCC volunteers. The evaluation results indicated an improvement in participants' understanding, as reflected by the increase in the average pre-test score from 48 to 68 in the post-test. These findings demonstrate that a structured socialization program effectively enhances volunteers' readiness, competence, and confidence in supporting the successful implementation of the ASEAN University Games 2024.